PENGARUH KAPASITAS SUMBER DAYA MANUSIA (KSDM) POLITIK PENGANGGARAN (PP), DAN PERENCANAAN PENGANGGARAN(PP) TERHADAP SINKRONISASI DOKUMEN APBD DENGAN DOKUMEN KUA PPAS DI LINGKUNGAN PEMERINTAH KOTA DUMAI - Inayatus Tsaniyah; Taufeni Taufik; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to determine the capacity of human resources, budgeting politics, and budget planning on the synchronization between Regional Revenue and Expenditures budget ( APBD) document and General Policy of Regional Revenues and expenditures budget (KUA) – Provisional Budget Celling Priority (PPAS) document. This study using purposive sampling method. The population in this study are civil servants Dumai city region, namely the commite agency (DPRD), Head of SKPD, Head of Area, Head of Section, Head of Sub Part, Head of Sub Area, and Staff that related to arranging budgeting of SKPD. Samples and this research is 94 respondents who have met the criteria for a sample. Data collection techniques used is by distributing questionnaires. Data were analyzed using multiple linear regression analysis with SPSS. This research proves that capacity of human resources, budgeting politics, and budget planning a significanton affect the sincronization beetwen APBD document with KUA-PPAS.Keywords: APBD, KUA-PPAS, Capacity of Human Resources, Budgeting Politicsand Budget Planning.